Prognostic factors related with outcomes in traumatic out-of-hospital cardiac arrest patients without prehospital return of spontaneous circulation: a nationwide observational study - Jun, Gwang Soo; Kim, Jae Guk; Choi, Hyun Young; Kang, Gu Hyun; Kim, Wonhee; Jang, Yong Soo; Kim, Hyun Tae (Clinical and experimental emergency medicine, 2020)
To evaluate the prognostic factors associated with the sustained return of spontaneous circulation (ROSC) and survival to hospital discharge in traumatic out-of-hospital cardiac arrest (TOHCA) patients without prehospital ROSC. We analyzed Korean nationwide data from the Out-of-Hospital Cardiac Arrest Surveillance, and included adult TOHCA patients without prehospital ROSC from January 2012 to December 2016. The primary outcome was sustained ROSC (>20 minutes). The secondary outcome was survival to discharge. Multivariate analysis was performed to investigate factors associated with the outcomes of TOHCA patients. Among 142,905 cases of OHCA, 8,326 TOHCA patients were investigated. In multivariate analysis, male sex (odds ratio [OR], 1.326; 95% confidence interval [CI], 1.103-1.594; P=0.003), and an initial shockable rhythm (OR, 1.956; 95% CI, 1.113-3.439; P=0.020) were significantly associated with sustained ROSC. Compared with traffic crash, collision (OR, 1.448; 95% CI, 1.086-1.930; P=0.012) was associated with sustained ROSC. Fall (OR, 0.723; 95% CI, 0.589- 0.888; P=0.002) was inversely associated with sustained ROSC. Male sex (OR, 1.457; 95% CI, 1.026-2.069; P=0.035) and an initial shockable rhythm (OR, 4.724; 95% CI, 2.451-9.106; P<0.001) were significantly associated with survival to discharge. Metropolitan city (OR, 0.728; 95% CI, 0.541-0.980; P=0.037) was inversely associated with survival to discharge. Compared with traffic crash, collision (OR, 1.745; 95% CI, 1.125-2.708; P=0.013) was associated with survival to discharge. Male sex, an initial shockable rhythm, and collision could be favorable factors for sustained ROSC, whereas fall could be an unfavorable factor. Male sex, non-metropolitan city, an initial shockable rhythm, and collision could be favorable factors in survival to discharge.